Penta Helix Model In Local Tourism Development Through “Peken Banyumasan” - Teddy Rusmawan; Denok Kurniasih; Anggara Setya Saputra; Devit Bagus Indranika (Universitas Sultan Ageng Tirtayasa, 2023)
The purpose of this study was to analyze and describe the Collaborative Penta Helix in the development of local tourism through Peken Banyumasan. The research method used is qualitative. An informant recruitment technique is purposive sampling. The data analysis technique used is an interactive model. The results show that the collaborative pentahelix conducted by the government sector, the private sector, and society as a whole is well coordinated and executed. The stakeholders have a definite role in the establishment of collaboration. The role of each stakeholder involved, such as the district government, as the government sector, has a role as a facilitator and organizer in Peken Banyumasan; academics at ITTP Telkom Purwokerto, as the private sector, have a role as drafters of Peken Banyumasan activities as well as implementers; the arts and culture community, as the private sector, has a role as a supporter of traditional handicrafts and tools to support and promote MSMEs in Banyumas Regency; and the mass media as supporting activities in the field of information and communication as a form of information dissemination in a wide scope.